Beer-Sheva Excavator Blasts Yadin—No Bama at Beer-Sheva - Rainey, Anson F. (The Biblical archaeology review, 1977)
This is in response to your article in the March 1977 issue about alleged bama at Beer-Sheva ("Yigael Yadin Finds a Bama at Beer-Sheva," BAR 03:01).